The Gülen Movement in London and the Politics of Public Engagement: Producing 'Good Islam' Before and After 15 July. (2nd January 2018) - Tee, Caroline
ABSTRACT: Since the failed coup of 15 July 2016, for which it is held responsible, the Gülen Movement (GM) has been in crisis. With no foreseeable future in its homeland, the GM is now tasked with regrouping abroad. This article investigates the GM in London, a city that, for various reasons, is likely to become a significant centre for Gülenist activity in the post-coup era. Taking the Dialogue Society (DS) as its focus, it investigates the prospects of the GM's survival by analyzing its activities, both before and after the coup, in light of Mamdani's discussion of 'good' and 'bad' Muslims in the post-9/11 world. The article shows how the GM has established itself as a voice of 'good' Islam in the context of British debates on Islam and radicalization. It suggests that the public presence the GM has established for itself through its public engagement activities in the UK could constitute a central part of its fight back against President Erdoğan, and be catalytic to its creation of a dynamic future in exile.